Sosialisasi Kesehatan Mental pada Kelas VII di SMP Negeri 17 Surakarta - Desy Rosiana; Dhian Riskiana Putri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Adolescence is a transitional period full of emotional, physical, and biological changes. Although physical health is often the main focus of teenagers, mental health is a more important aspect to maintain. Balanced mental health can contribute to a person's happiness in life. However, in Indonesia, even though there is Law No. 18 of 2014 concerning Mental Health, mental health problems are still often ignored. Bullying is one of the factors that can damage teenagers' mental health. At SMP Negeri 17 Surakarta, bullying has become a problem that affects the mental well-being of students, both as perpetrators and victims. For this reason, community service with the theme "Socialization of Mental Health in Class VII at SMP Negeri 17 Surakarta" was carried out to increase students' awareness about the importance of maintaining mental health and the negative impact of bullying. This activity was carried out in four stages: presentation of material about mental health and bullying, group discussions, making positive affirmations, and giving rewards to participants. The results of this activity show that students understand the relationship between bullying and mental health disorders, and are aware of the long-term impacts of bullying behavior. This activity succeeded in attracting students' attention and increasing their awareness about the importance of maintaining mental health, with the hope of creating a healthier school environment free from bullying.